2013
DOI: 10.1080/1573062x.2013.765488
|View full text |Cite
|
Sign up to set email alerts
|

A review of frontier approaches to efficiency and productivity measurement in urban water utilities

Abstract: Despite the rapid global revitalisation of urban water policy, and the universal need to measure and improve organizational efficiency and productivity in all suppliers as a means of ensuring the sustainability of this key resource, only recently have the most advanced econometric and mathematical programming frontier techniques been applied to urban water utilities. This paper provides a synoptic survey of the comparatively few empirical analyses of frontier efficiency and productivity measurement in urban wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Saal et al, 2007;Bottaso and Conti, 2009;Portela et al, 2011;Maziotis et al, 2014). Because of the advantages of benchmarking, studies on the efficiency and growth in the productivity of water utilities have also been carried out in other countries, such as Portugal (Carvalho et al, 2012), Australia (Worthington, 2014), Spain (Sala-Garrido et al, 2012), Italy (Guerrini et al, 2013), and France (Lannier and Porcher, 2014), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Saal et al, 2007;Bottaso and Conti, 2009;Portela et al, 2011;Maziotis et al, 2014). Because of the advantages of benchmarking, studies on the efficiency and growth in the productivity of water utilities have also been carried out in other countries, such as Portugal (Carvalho et al, 2012), Australia (Worthington, 2014), Spain (Sala-Garrido et al, 2012), Italy (Guerrini et al, 2013), and France (Lannier and Porcher, 2014), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Alsharif et al (2008) studied the spatial difference of water supply systemic ratios in Palestine and suggested that the systemic water supply efficiency of the Gaza region was less than that of the West Bank, attributing this difference primarily to the leakage rate of pipe nets. Worthington (2014) reviewed the literature concerning urban water system efficiency over the past 20 years, indicating that ownership and regulations were the main influencing factors. Meanwhile, models of resource optimization configuration gradually matured based on DEA models, and these studies concentrated on aspects of water resource configuration optimization (Li et al, 2013, Wu et al, 2013 and scientific resource management (Hu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, efficient companies should be used as a reference to improve the performance of inefficient units. Because of its usefulness, in recent years, several studies have conducted to measure the efficiency of the water and sewerage industry in different countries such as the UK (Molinos- Senante et al 2014b), Portugal (Carvalho and Marques 2014), Australia (Worthington 2014), Italy (Guerrini et al 2013), Peru (Berg and Lin 2008), India (Gupta et al 2012), Spain , and France (Lannier and Porcher 2014).…”
Section: Introductionmentioning
confidence: 99%